Effect of Calving Interval on Milk Yield in Italian Buffalo Population (Journal of Buffalo Science, 2016)
The objective of this study was to investigate the effect of the previous calving intervals (CI) on milk yield (MY) in the current lactation for the Italian buffalo breed population.Data for 86,585 lactation records from the Italian Buffalo Breeders Association database, were analyzed. MY BLUP-estimates were obtained by including in the Animal Model the fixed effects of age-parity, previous CI, and herd-contemporary-group. The MY solutions for the months of CI were analyzed with the linear regression model where CI in months was the explanatory variable. 59.66% of the lactation records had CI between 11 and 14 months. 37.91 % of the lactation records were distributed between 15 and 24 months. The smaller percentage of records showed CI greater than 24 months. This CI distribution may be, in part, the result of herd management strategies. Dairy producers try to shorten the CI of their herd in order to get the most profit from early conceptions of the buffalo. The regression model and its parameters were statistically significant. The coefficient of determination was equal to 0.58. The intercept was equal to 72.42 kg; and the linear coefficient (b) was equal to -3.43. The negative value of b denotes a negative effect of CI on MY. This result indicates that there is a negative linear relationship between previous CI and MY in the current lactation. Therefore, shorten the CI may increase the profits of the farm through higher MY, because it has less of a negative effect on MY than longer CI.